2021
DOI: 10.1061/(asce)su.1943-5428.0000336
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Independent Baseline Searching for Global GNSS Networks

Abstract: An n-station continuously operated global navigation satellite system (GNSS) network contains n-1 independent baselines. Baseline structure is critical to positioning accuracy, and the final result is dependent on the baseline selection strategies. The baseline length and amount of common observations are the primary principles for baseline selection. However, there are few discussions about the optimal strategy to determine the independent baseline of a huge GNSS network. To enhance the performance of the mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…A study has identified the concept that the constellation optimization of pseudolites can influence the pseudolite positioning error [123]. The essence of constellation optimization is to make a larger number of satellites observable in more space to improve positioning precision [124,128]. The effectiveness of a multi-objective particle swarm-based approach for the deployment optimization of pseudolite systems is discussed [129].…”
Section: Constellation Optimizationmentioning
confidence: 99%
“…A study has identified the concept that the constellation optimization of pseudolites can influence the pseudolite positioning error [123]. The essence of constellation optimization is to make a larger number of satellites observable in more space to improve positioning precision [124,128]. The effectiveness of a multi-objective particle swarm-based approach for the deployment optimization of pseudolite systems is discussed [129].…”
Section: Constellation Optimizationmentioning
confidence: 99%
“…The data was processed with the Bernese software developed at the Astronomical Institute of the University of Bern (AIUB). Detailed descriptions or flow charts of data processing with Bernese can be found in the Bernese manual [8] or other publications [12,14,[16][17][18]. The products were downloaded and used following the website (https://cddis.nasa.gov/Data_and_Derived_Products/GNSS/GNSS_product_holdings.ht ml, Weihai, China, 1 June 2018) and the instruction of Bernese [8].…”
Section: Datamentioning
confidence: 99%
“…WEIGHT is a synthesis of these two strategies. In this process, a normalization is introduced since the dimensions of OBS-MAX (number) and SHORTEST (meter) are not consistent [14]. Unfortunately, WEIGHT is still an empirical operation lacking theoretical support.…”
Section: The Criteria-distance Observation and Othersmentioning
confidence: 99%
See 2 more Smart Citations